Russian Science Foundation grant No. 20-14-00140 supported this study. The authors are thankful to the multi-access Center “Bioinformatics” for the use of computational resources as supported by Russian government project FWNR-2022-0020 and the Russian Federal Science and Technology Program for the Development of Genetic Technologies. - O. V. Vishnevsky; I. V. Chadaeva; E. B. Sharypova; B. M. Khandaev; K. A. Zolotareva; A. V. Kazachek; P. M. Ponomarenko; N. L. Podkolodny; D. A. Rasskazov; E. V. Zemlyanskaya; A. G. Bogomolov; O. A. Podkolodnaya; et al. (Вавиловский журнал генетики и селекции)
It is generally accepted that during the domestication of food plants, selection was focused on their productivity, the ease of their technological processing into food, and resistance to pathogens and environmental stressors. Besides, the palatability of plant foods and their health benefits could also be subjected to selection by humans in the past. Nonetheless, it is unclear whether in antiquity, aside from positive selection for beneficial properties of plants, humans simultaneously selected against such detrimental properties as allergenicity. This topic is becoming increasingly relevant as the allergization of the population grows, being a major challenge for modern medicine. That is why intensive research by breeders is already underway for creating hypoallergenic forms of food plants. Accordingly, in this paper, albumin, globulin, and βamylase of common wheat Triticum aestivum L. (1753) are analyzed, which have been identified earlier as targets for attacks by human class E immunoglobulins. At the genomic level, we wanted to find signs of past negative selection against the allergenicity of these three proteins (albumin, globulin, and βamylase) during the domestication of ancestral forms of modern food plants. We focused the search on the TATAbinding protein (TBP)binding site because it is located within a narrow region (between positions –70 and –20 relative to the corresponding transcription start sites), is the most conserved, necessary for primary transcription initiation, and is the beststudied regulatory genomic signal in eukaryotes. Our previous studies presented our publicly available Web service Plant_SNP_TATA_Ztester, which makes it possible to estimate the equilibrium dissociation constant (KD) of TBP complexes with plant proximal promoters (as output data) using 90 bp of their DNA sequences (as input data). In this work, by means of this bioinformatics tool, 363 gene promoter DNA sequences representing 43 plant species were analyzed. It was found that compared with nonfood plants, food plants are characterized by significantly weaker affinity of TBP for proximal promoters of their genes homologous to the genes of commonwheat globulin, albumin, and βamylase (food allergens) (p< 0.01, Fisher’s Ztest). This evidence suggests that in the past humans carried out selective breeding to reduce the expression of food plant genes encoding these allergenic proteins.